COLUMN PRECONCENTRATION OF URANIUM BY 1 -(2-PY RIDYLAZ0)-2-NAPHTHOL SUPPORTED ON NAPHTHALENE USING DIF'FERENTLAL PULSE POLAROGRAPHY (Journal of Sciences, Islamic Republic of Iran)
A solid chelating material, 1-(2-pyridy1azo)-2-naphthol (PAN) supported on naphthalene provides a rapid and highly selective means of preconcentration of uranium from aqueous solution. Uranium is quantitatively retained on this adsorbent in the pH range 9.8-10.7 with a flow rate of 1 ml min . The metal complex was desorbed with 10 ml of 2 M hydrochloric acid and uranium is determined by differential pulse polarography (DPP). The detection limit is 1.5 µg ml (Signal to noise ratio = 2). The linearity is maintained in the concentration range 3.0 - 310 ) µ g ml with a correlation coefficient of 0.9994 (n=7) and relative standard deviation of 1.1 %(n=7). Characterization of the electroactive process included an examination of the degree of reversibility. Various parameters such as the effect of pH, volume of aqueous phase and interference of a number of metal ions on the determination of uranium have been studied in detail to optimize the conditions for determination of uranium.